THE USE OF COMMUNICATION STRATEGY IN INTENSIVE ENGLISH CLASSROOM - ria, Guspa (Menara Ilmu, 2018)
Communication strategy is the way to help the speakers when facing difficulties incommunication using Foreign Language (English). When leaners do not know how to say aword in English, they can communicate effectively by using their hands, imitating sounds,inventing new words, or describing what they mean. These ways are the kinds ofcommunicating with communication strategies. This paper is focused on the use ofcommunication strategy in Intensive English classroom. It also describes the theory ofcommunication strategies that can be used for learners in Intensive English classroom. Theaim of this paper is to provide several ways of communication strategies that can be used forteacher in classroom and to facilitate learners’ communicative competence in English.Key words: communication strategy, Intensive English classroom, communicativecompetence.